Lane 2005 Reconstruction of a Temperature Time Series for Linnédalen, Svalbard - ACADIS Community Support (Arctic Data Center, 2013)
Abstract: A temperature time series has been reconstructed for the period from 1974 to 2004 at Linnédalen, Svalbard (78°N latitude, Norway). A method for extending the time series back to the early 20th Century is also presented. This reconstruction is important as a surrogate instrumental record in a region of low observation density and high observation value. As an important site of paleoclimate research, Linnédalen’s meteorological record is essential to calibrating a multi-century record of regional climate change. Lake Linné, a glacial lake situated in the valley of Linnédalen, provides researchers with a high-resolution sediment record of climate change during the late Holocene. To better interpret this record, limited local meteorological data from the Valley have been coupled with longer regional weather records to develop an extended meteorological record for the location. The reconstruction and methods used are presented and assessed and recommendations for further work are provided. This project is part of the Svalbard Research Experience for Undergraduates (REU) program sponsored by the National Science Foundation.